1986
DOI: 10.1128/jcm.24.6.986-990.1986
|View full text |Cite
|
Sign up to set email alerts
|

Aeration selects for mucoid phenotype of Pseudomonas aeruginosa

Abstract: A mucoid strain of Pseudomonas aeruginosa isolated from a patient with cystic fibrosis and its nonmucoid revertant were grown in a chemically defined alginate-promoting medium under batch and continuous culture conditions. Selection for the mucoid and nonmucoid phenotype was accomplished by varying the levels of air available to the culture. The addition of air at a rate of 0.5 liters/min to the nonmucoid revertant growing under batch or continuous culture conditions resulted in a greater than 50% decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Culture media. A modification of the chemically defined alginate-promoting (AP) medium of Mian et al (25), which has been described previously (17,18), was the primary growth medium used for the chemostat studies. The medium contained 100 mM monosodium glutamate, 100 mM sodium gluconate, 7.5 mM NaH2PO4, 16.3 mM K2HPO4, and 10 mM MgSO4 7H20.…”
Section: Methodsmentioning
confidence: 99%
“…Culture media. A modification of the chemically defined alginate-promoting (AP) medium of Mian et al (25), which has been described previously (17,18), was the primary growth medium used for the chemostat studies. The medium contained 100 mM monosodium glutamate, 100 mM sodium gluconate, 7.5 mM NaH2PO4, 16.3 mM K2HPO4, and 10 mM MgSO4 7H20.…”
Section: Methodsmentioning
confidence: 99%
“…MEP lot 1 was prepared from organisms grown in deoxycholate citrate broth, a medium shown by Govan to stabilize MEP production (8). MEP lot 2 was obtained from the same strain cultured in modified Mian's medium, as described by Krieg et al (11). We employed one additional modification of this medium, which was to substitute Lglutamine for monosodium glutamate as the nitrogen source.…”
Section: Methodsmentioning
confidence: 99%
“…Together, our results demonstrated that sodium sulfate can suppress alginate production in mucoid P. aeruginosa strains. Environmental factors that influence bacterial growth, such as temperature (Leitao et al, 1992) and oxygen potential (Krieg et al, 1986), were reported to play roles in alginate production. We therefore explored whether suppressed alginate production is associated with altered bacterial growth by sodium sulfate.…”
Section: Resultsmentioning
confidence: 99%